A facile strategy for fabricating composite patch scaffold by using porcine acellular dermal matrix and gelatin for the reconstruction of abdominal wall defects. (May 2020) - Liu, Suihong; Zhang, Haiguang; Hu, Qingxi; Zhang, Chuck; Li, Shuai; Wang, Ben
Defects of the abdominal wall continue to be a significant issue in regenerative medicine and tissue engineering. Porcine acellular dermal matrix (P-ADM) and gelatin have been widely used for fabricating engineered abdominal wall due to their good biocompatibility and integration with host tissues. In this study, we demonstrate a novel and reproducible approach of using gelatin and P-ADM powder to fabricate composite patch scaffolds by combining solvent casting and enzymatic cross-linking for the abdominal wall regeneration in rats. Different concentration ratios of gelatin and P-ADM and different shapes of engineered scaffolds are studied for various abdominal wall defects. Skeletal muscle cells and human umbilical vein endothelial cells can successfully attach to the surface of the scaffolds and maintain high viability after culturing for five days. In vivo experiments demonstrate that there are no signs of infection, intra-abdominal adhesion, and severe inflammation after two weeks, which indicate good repairability of the scaffolds. In conclusion, we propose a novel method that holds great potential for building engineered scaffolds to meet the different requirements of abdominal wall regeneration.